A review of the techniques to measure the hermeticity of glass frit encapsulated solar cells - Jorge Martins (2021)
Emerging 3rd generation photovoltaic technologies such as perovskite and dye-sensitized solar cells are very attractive for commercialization mainly due to their low-cost materials and fabrication processes. The main drawback of these devices is their poor long-term stability. To increase the long-term stability of these devices, a hermetic encapsulation is required. The hermeticity of encapsulated devices are measured and characterized using hermeticity tests according to standard test procedures. A review of the several techniques to measure the hermeticity is presented, addressing the test methods, limitations and applicability to perovskite and dye-sensitized solar cells glass frit encapsulated devices.